(untitled) (Editora Impacto Científico, 2026)
INTRODUCTION: Breast cancer (BC) is a series of malignancies that affect the mammary gland, being the most common cancer in the world. In 2023, in Brazil, the incidence was 42 cases per 100,000 women. Modifiable risk factors include lifestyle, and non-modifiable risk factors include advancing age and genetic alterations, the main genes being BRCA1 and BRCA2. OBJECTIVE: This review aims to analyze the mutations of the main BC genes, BRCA1 and BRCA2, and their relevance in medical practice. METHODS: Articles in English and Portuguese published in the last 5 years in the PubMed and Scielo databases were selected using the keywords: breast cancer, genes, and BRCA1 and BRCA2. RESULTS: Data elucidate that approximately 5 to 10% of BC cases are related to heredity, and 30% of BC patients had a positive family history. These are tumor suppressor genes responsible for the correct processing of DNA strands. When these genes repair DNA strands improperly, apoptosis occurs, which is insufficient to contain potentially oncogenic multiplication. Furthermore, approximately 75% of mutations can occur throughout life due to lifestyle and vary according to penetrance. The two genes are the most relevant, since BRCA1 has a risk of developing breast cancer of about 57 to 65% and an estimated 20 to 50% risk of ovarian cancer. While for BRCA2 the estimates are 35 to 57% and 5 to 23%, respectively; moreover, they can favor oncogenesis in other locations such as the fallopian tubes, ovaries, peritoneum, and pancreas, and in BRCA2, also melanoma. The importance of identifying these mutations lies in the possibility of clinical repercussions, such as the decision to perform risk-reducing bilateral mastectomy, oophorectomy, or annual screening with magnetic resonance imaging or transvaginal ultrasound with annual or semi-annual Doppler Doppler, or chemoprophylaxis with Tamoxifen. Another application of genetic testing is the discussion about the use of platinum agents or polymerase inhibitors for cancer treatment, in addition to strategies such as risk-reducing contralateral mastectomy; due to these factors, the use of these tests has been increasing. CONCLUSION: In summary, breast cancer is the most common cancer in the world and is related to heredity and mutations in the BRCA1 and BRCA2 genes, which are tumor suppressors. Besides breast cancer, these genes cause neoplasms in other sites, and the recognition of their mutations allows for a better clinical approach in treatment. DOI: https://doi.org/10.56238/edimpacto2025.090-095